(3SOjO GdUhGH aj EOQGc JYQja GdcJGHs - (3eMeO GdbdGQjfj GdeMdj GdTGaYj Hf Ydjs
(3ChdgG (B:s
(3GdMeO ddg Pi GdCaYGd hGdEfYGe agPg fHPI dWjaI HEYdGe eG JVefJg ef OQQ GdYHGQGJ efjaI de JSHb HeG ajgG ef ZQQ GdETGQGJ s
(3BNQgG (B:s
(3hYcSgG GdNGJejI ef GdNJe , hgh GdWHY HWGHY Ydi GdTF UjGfI dg , Ke fbHJ Edi eG jaQZ efg , hGdefGSHI LdjdI , dCf GdeWHhY aQZ efg cPdc s
(3HgG fXGe GdJYbjHIs
(3aQZ GdeDda ef JCdjag (B1219(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjIOGQ GdcJH GdeUQjI (B((3eLGejY (B43) s
Keywords: (3GddZIs